Upaya Meningkatkan Hasil Belajar IPS melalui Model Pembelajaran Kooperatif Tipe Jigsaw bagi Peserta Didik Kelas IV SDN-2 Kasongan Baru Tahun Pelajaran 2016/2017: Efforts to Improve Social Studies Learning Outcomes through the Jigsaw Cooperative Learning Model for Class IV Students of SDN-2 Kasongan New 2016/2017 Academic Year - Elda Elda; Suniati Suniati (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This study aims to: (1) To determine the activity of students in social studies by using the Cooperative Type Jigsaw learning model, (2) To determine the increase in social studies learning outcomes with the Jigsaw Cooperative learning model for students in Class IV SDN-2 Kasongan Baru Katingan Hilir Subdistrict, Katingan Regency. The type of this research is to use a class action research design (PTK) that tries to solve or answer the problems faced in the current situation with the research subjects of all students in class IV SDN - 2 Kasongan Baru totaling 12 people, the data collection techniques used are observation and test. The data analysis technique uses qualitative and quantitative techniques.